Plant physiological and environmental controls over the exchange of acetaldehyde between forest canopies and the atmosphere - Jardine, K; Harley, P; Karl, T; Guenther, A; Lerdau, M; Mak, J E (BIOGEOSCIENCES, 2008)
We quantified fine scale sources and sinks of gas phase acetaldehyde in two forested ecosystems in the US. During the daytime, the upper canopy behaved as a net source while at lower heights, reduced emission rates or net uptake were observed. At night, uptake generally predominated throughout the canopies. Net ecosystem emission rates were inversely related to foliar density due to the extinction of light in the canopy and a respective decrease of the acetaldehyde compensation point. This is supported by branch level studies revealing much higher compensation points in the light than in the dark for poplar (Populus deltoides) and holly oak (Quercus ilex) implying a higher light/temperature sensitivity for acetaldehyde production relative to consumption. The view of stomata as the major pathway for acetaldehyde exchange is supported by strong linear correlations between branch transpiration rates and acetaldehyde exchange velocities for both species. In addition, natural abundance carbon isotope analysis of gas-phase acetaldehyde during poplar branch fumigation experiments revealed a significant kinetic isotope effect of 5.1 +/- 0.3 parts per thousand associated with the uptake of acetaldehyde. Similar experiments with dry dead poplar leaves showed no fractionation or uptake of acetaldehyde, confirming that this is only a property of living leaves. We suggest that acetaldehyde belongs to a potentially large list of plant metabolites where stomatal resistance can exert long term control over both emission and uptake rates due to the presence of both source(s) and sink(s) within the leaf which strongly buffer large changes in concentrations in the substomatal airspace due to changes in stomatal resistance. We conclude that the exchange of acetaldehyde between plant canopies and the atmosphere is fundamentally controlled by ambient acetaldehyde concentrations, stomatal resistance, and the compensation point which is a function of light/temperature.
APS
Keywords: acetaldehydes; emission; Populus deltoides; Quercus ilex; stomatal resistance

Biogenic volatile organic compounds (VOC): An overview on emission, physiology and ecology - Kesselmeier, J; Staudt, M (JOURNAL OF ATMOSPHERIC CHEMISTRY, 1999)
This overview compiles the actual knowledge of the biogenic emissions of some volatile organic compounds (VOCs), i.e., isoprene, terpenes, alkanes, alkenes, alcohols, esters, carbonyls, and acids. We discuss VOC biosynthesis, emission inventories, relations between emission and plant physiology as well as temperature and radiation, and ecophysiological functions. For isoprene and monoterpenes, an extended summary of standard emission factors, with data related to the plant genus and species, is included. The data compilation shows that we have quite a substantial knowledge of the emission of isoprene and monoterpenes, including emission rates, emission regulation, and biosynthesis. The situation is worse in the case of numerous other compounds (other VOCs or OVOCs) being emitted by the biosphere. This is reflected in the insufficient knowledge of emission rates and biological functions. Except for the terpenoids, only a limited number of studies of OVOCs are available; data are summarized for alkanes, alkenes, carbonyls, alcohols, acids, and esters. In addition to closing these gaps of knowledge, one of the major objectives for future VOC research is improving our knowledge of the fate of organic carbon in the atmosphere, ending up in oxidation products and/or as aerosol particles.
Keywords: acids; alkanes; alkenes; carbonyls; ecology; emission; emission inventories; Esters; isoprene; nonmethane hydrocarbons; oxygenated compounds; physiology; review; terpenes; Volatile Organic Compounds